1997
DOI: 10.1038/386827a0
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between subjective effects of cocaine and dopamine transporter occupancy

Abstract: Cocaine is believed to work by blocking the dopamine transporter (DAT) and thereby increasing the availability of free dopamine within the brain. Although this concept is central to current cocaine research and to treatment development, a direct relationship between DAT blockade and the subjective effects of cocaine has not been demonstrated in humans. We have used positron emission tomography to determine what level of DAT occupancy is required to produce a subjective 'high' in human volunteers who regularly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
389
2
9

Year Published

1999
1999
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 585 publications
(421 citation statements)
references
References 21 publications
21
389
2
9
Order By: Relevance
“…The D2R has been implicated in cocaine addiction, as well as cocaine craving, in humans [19][20][21][22]. Therefore, the D2R may provide a target for prevention of relapse after cocaine detoxification, and the study of striatal D2R availability in mouse models of cocaine addiction is important to unravel its role in human cocaine addiction.…”
Section: Amphetamine-induced Dopamine Releasementioning
confidence: 99%
“…The D2R has been implicated in cocaine addiction, as well as cocaine craving, in humans [19][20][21][22]. Therefore, the D2R may provide a target for prevention of relapse after cocaine detoxification, and the study of striatal D2R availability in mouse models of cocaine addiction is important to unravel its role in human cocaine addiction.…”
Section: Amphetamine-induced Dopamine Releasementioning
confidence: 99%
“…The relevance of the DAT in the abuse liability of cocaine is supported further by neuroimaging studies. In human cocaine users, a significant correlation was observed between the level of DAT occupancy and the magnitude of the subjective high following administration of cocaine (Volkow et al, 1997) or the behavioral stimulant methylphenidate (Volkow et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…However, in order to produce equivalent increases in locomotor activity in rodents, selective DAT inhibitors must exhibit greater occupancy of DAT than does the nonselective monoamine transporter inhibitor cocaine (Rothman et al, 1992;Vaugeois et al, 1993). Neuroimaging studies in humans have found a significant correlation between DAT occupancy and the subjective high following administration of cocaine (Volkow et al, 1997) or methylphenidate . However, DAT inhibitors differ in their effectiveness as positive reinforcers.…”
Section: Introductionmentioning
confidence: 99%